2019
DOI: 10.1038/s41598-019-45784-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in porcine uterus and serum are affected by zearalenone and represent a new target for mycotoxin biomarker discovery

Abstract: The mycotoxin zearalenone (ZEN) poses a risk to animal health because of its estrogenic effects. Diagnosis of ZEN-induced disorders remains challenging due to the lack of appropriate biomarkers. In this regard, circulating microRNAs (small non-coding RNAs) have remarkable potential, as they can serve as indicators for pathological processes in tissue. Thus, we combined untargeted and targeted transcriptomics approaches to investigate the effects of ZEN on the microRNA expression in porcine uterus, jejunum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Yet, the opposite effects seen between the piglets fed ZEN and DHZEN deserve further investigations. As briefly discussed in Grenier et al [11], the lack of effects observed on the ERα is in agreement with Oliver et al [54], who analyzed the gene and protein expression of ERs in the uterus of piglets exposed to 1.5 mg/kg of ZEN for four weeks. However, Oliver et al reported a two-fold increase in the mRNA level of ERβ in those animals, which could not be confirmed in the present experiment.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Yet, the opposite effects seen between the piglets fed ZEN and DHZEN deserve further investigations. As briefly discussed in Grenier et al [11], the lack of effects observed on the ERα is in agreement with Oliver et al [54], who analyzed the gene and protein expression of ERs in the uterus of piglets exposed to 1.5 mg/kg of ZEN for four weeks. However, Oliver et al reported a two-fold increase in the mRNA level of ERβ in those animals, which could not be confirmed in the present experiment.…”
Section: Discussionsupporting
confidence: 84%
“…None of the treatments significantly affected the body weight of animals (Table 1). While ZEN caused a time-dependent increase of the vulva size, reaching an enlargement by a factor of 3.3 compared to the control group on day 27 [11], neither HZEN nor DHZEN influenced the vulva size during the experimental period. Similarly, the reproductive tract weight at the end of the experiment was markedly increased in the ZEN group, whereas the ZEN metabolites showed no effect on this parameter (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations